TANYSTROPHEUS (ARCHOSAUROMORPHA, PROLACERTIFORMES) REMAINS FROM THE TRIASSIC OF THE NORTHERN FRIULI (NE ITALY) - FABIO MARCO DALLA VECCHIA (Rivista Italiana di Paleontologia e Stratigrafia, 2000)
The first diagnostic remains of the large prolacertiform Tanystropheus are reported from northeastern Italy. They include a proximal caudal vertebra from the Middle Triassic of Aupa valley (Udine, Friuli) and a cervical vertebra from the Carnian of Fusea (Udine). The cervical vertebra represents the first record of Tanystropheus in the Carnian and is the geologically youngest occurrence other than the Norian T. fossai. Tanystropheus lived along the coasts of the northwestern Tethys during the Late Triassic while it disappeared in Central Europe where continental environments were prevailing.